2022
DOI: 10.3390/molecules27072060
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Stimulated Darkening from UV-C Light on Different Bean Genotypes by NMR Spectroscopy

Abstract: The use of UV-C cool white light on bean (Phaseolus vulgaris L.) seeds significantly increases the biochemical seed coat post-harvest darkening process, whilst preserving seed germination. The aim of this work consists in monitoring the effect caused by the incidence of UV-C light on different bean genotypes using NMR spectroscopy. The genotype samples named IAC Alvorada; TAA Dama; BRS Estilo and BRS Pérola from the Agronomic Institute (IAC; Campinas; SP; Brazil) were evaluated. The following two methodologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The HSQC correlations of signals at δ C 103.0; 98.5; 96.4; 95.9 and 92.1 ppm, with protons at δ H 4.44 (d, 7.6); 4.90 (brs); 4.60 (d, 7.4); 4.66 (d, 7.6) and 5.25 (d, 3.8) ppm respectively, indicate the presence of other saccharides in minor amounts. Other metabolites detected were: isethionic acid ( Barrow et al., 1993 ), acetic acid ( Sciubba et al., 2020 ), formic and lactic acid ( Ponder and Richards, 1993 ) and the amino acids alanine ( Sciubba et al., 2020 ), valine ( Ryu et al., 2016 ), threonine ( Salvador et al., 2022 ) and N,N-dimethyltaurine ( Blunden et al., 1986 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSQC correlations of signals at δ C 103.0; 98.5; 96.4; 95.9 and 92.1 ppm, with protons at δ H 4.44 (d, 7.6); 4.90 (brs); 4.60 (d, 7.4); 4.66 (d, 7.6) and 5.25 (d, 3.8) ppm respectively, indicate the presence of other saccharides in minor amounts. Other metabolites detected were: isethionic acid ( Barrow et al., 1993 ), acetic acid ( Sciubba et al., 2020 ), formic and lactic acid ( Ponder and Richards, 1993 ) and the amino acids alanine ( Sciubba et al., 2020 ), valine ( Ryu et al., 2016 ), threonine ( Salvador et al., 2022 ) and N,N-dimethyltaurine ( Blunden et al., 1986 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of each metabolite was confirmed by comparing its spectroscopic data with those previously described in the literature. NMR spectra analysis of the extract of B. hamifera in D 2 O indicated that this extract contains a complex mixture of metabolites, among which floridoside (Ye et al, 2013) (Barrow et al, 1993), acetic acid (Sciubba et al, 2020), formic and lactic acid (Ponder and Richards, 1993) and the amino acids alanine (Sciubba et al, 2020), valine (Ryu (Salvador et al, 2022) and N,Ndimethyltaurine (Blunden et al, 1986). The 1D and 2D NMR spectra analysis of G. rugosa extract in D 2 O showed that this extract also contained a complex mixture of metabolites, including N,N,N-trimethyl taurine (King et al, 1982), N,N-dimethyltaurine, N-monomethyltaurine (McCusker and Klinman, 2009) and taurine (Ye et al, 2013), as well as isethionic acid and floridoside.…”
Section: Chemical Analysis Of Crude Extractsmentioning
confidence: 99%
“…At a metabolic level, besides being an energy substrate, sugars work as signals of the disease activating PTI and ETI (Chen et al., 2019, 2020; Xue et al., 2015, 2021). In a study with NMR, it was possible to detect that the ‘BRS Estilo’ and ‘BRS Pérola’ carioca tegument genotypes, which have phenotypic characteristics of dark grain and greater resistance to Fop, presented higher concentrations of α‐glucose and β‐glucose (Salvador et al., 2022). Chen et al.…”
Section: Physical and Chemical Changes In Response To Fop In Resistan...mentioning
confidence: 99%
“…The infrared spectroscopy and imaging papers are as follows: Aykas et al [8] develop a rapid, accurate method to detect acrylamide content in par-frozen French fries using a portable Infrared spectrometer. Ren et al [9] use Fourier transform infrared spectroscopy to study the stability and interactions of anthocyanins and whey proteins. Finally, Jiang et al [10] develop a hyperspectral method, from 400 to 1000 nm, to rapidly and accurately discriminate the maturity stages of Camellia oleifera fruits.…”
mentioning
confidence: 99%